2007
DOI: 10.1007/s00125-007-0655-7
|View full text |Cite
|
Sign up to set email alerts
|

Early-onset type 2 diabetes in obese white subjects is characterised by a marked defect in beta cell insulin secretion, severe insulin resistance and a lack of response to aerobic exercise training

Abstract: Aims/hypothesis Early-onset type 2 diabetes is associated with marked visceral obesity and extreme insulin resistance, but its pathogenesis and response to treatment are not completely understood. We studied physical fitness, wholebody and hepatic glucose turnover, and insulin secretion in young obese Irish subjects before and after 3 months of aerobic exercise training. We hypothesised that exercise alone, with stable diet, should improve insulin sensitivity. Materials and methods Anthropometric parameters an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
74
1
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 39 publications
9
74
1
1
Order By: Relevance
“…These patients have a phenotype very similar to those reported above in previous studies [1][2][3][4][5]. All participants underwent a series of neuropsychological tests and brain magnetic resonance imaging studies.…”
supporting
confidence: 61%
See 2 more Smart Citations
“…These patients have a phenotype very similar to those reported above in previous studies [1][2][3][4][5]. All participants underwent a series of neuropsychological tests and brain magnetic resonance imaging studies.…”
supporting
confidence: 61%
“…Young patients with type 2 diabetes have been shown to have higher rates of hypertension and microalbuminuria than age-matched peers who have type 1 diabetes, despite better metabolic control and a shorter duration of diabetes [3]. We and others have shown that young obese patients with this phenotype are severely insulin resistant (even when compared with equally obese non-diabetic peers of similar age) and have a characteristic dyslipidaemia, with low HDL-cholesterol and elevated fasting triacylglycerol [2,4]. It has recently been shown that young type 2 diabetic patients also have blunted or absent metabolic and fitness responses to aerobic exercise training, associated with abnormalities in key muscle mitochondrial regulatory responses to exercise [4,5].…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…These findings were based on post hoc analyses from the intervention arm. Burns et al (2007) 363 examined the effects of a 3-month aerobic exercise training programme in young obese insulin-resistant subjects with and without T2DM. They recruited 13 subjects with T2DM and 18 non-diabetic control subjects for the baseline study.…”
Section: Methodsmentioning
confidence: 99%
“…Insulin resistance is a major contributor to development of the disease and to its complications [6][7][8].…”
mentioning
confidence: 99%